(3cJGH GdYde GdWHjYis
(3ChdgG (B:s
(3GdYde GdWHjYi gh eG jJHUQ HPhGJ GdCTjGA GdWHjYjI hdQGMJgG hehVhYg GdNGU gh GdCLSGe GdehLhOI HeG gi hGbYI ai GdJZjjQ s
(3BNQgG (B:s
(3hHPdc dg OdGFd YOjOI bO LRfG Yf PcQgG gQHkG ef GdESgGH HGdcdGe Je BNQ eG ai GdWHjYjGJ hGdMeO ddg GdhGgH GdYbd HdG fgGjI Bejf s
(3HgG fXGe GdJYbjHIs
(3HBNQgG agQS ddcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdadSaI hGdefWbs